Faktor Yang Mempengaruhi Struktur Modal Industri Dasar Kimia Yang Terdaftar Di BEI - Yovita Veridiana, Jonnardi (Jurnal Paradigma Akuntansi, 2019)
The purpose of this study is to see the effect of profitability, company growth, and liquidity on capital structure. there is another purpose, namely to determine the effect of profitability which is moderated by the inflation rate on the capital structure of basic and chemical industry companies in the Indonesia Stock Exchange (IDX) for the period 2013-2017. This study uses 260 data from 52 companies from basic industrial and chemical companies for five consecutive years. The method used is purposive sampling. The results of this study indicate that profitability has a negative significant effect and company growth has a positive significant influence on capital structure, while liquidity has no influence on the company's capital structure. Only profitability that has a profit if moderated by the inflation rate.